REDESIGN OF CURRICULUM AND SATISFACTION OF STUDENTS - PINO APABLAZA, Fernando (2021)
This eduactional research had like a espace scenery the proffesional school of tourism and hostelry business management, ubicated in the city of Lima. The educational research started in May 2017. The main target, was demonstrate that the application of the new design of curriculum was one of factors to contributed to increase the satisfaction levels of students of the profesional career. Also, the redesign of curriculum was analyzed by areas. The results of satisfaction levels of students were compared with the results of others students that used other different previous version of curriculum, and was demostrated through the Anova and T student analysis, both of them in 0.05 % of significance, that exist enough evidences to affirm, until proven otherwise, that the redesign curriculum was the cause that provoked the effects in the satisfaction students levels.